ER–plasma membrane contact sites contribute to autophagosome biogenesis by regulation of local PI3P synthesis - Nascimbeni, Anna Chiara; Giordano, Francesca; Dupont, Nicolas; Grasso, Daniel; Vaccaro, Maria I; Codogno, Patrice; Morel, Etienne (The EMBO journal, 2017)
The double‐membrane‐bound autophagosome is formed by the closure of a structure called the phagophore, origin of which is still unclear. The endoplasmic reticulum (ER) is clearly implicated in autophagosome biogenesis due to the presence of the omegasome subdomain positive for DFCP1, a phosphatidyl‐inositol‐3‐phosphate (PI3P) binding protein. Contribution of other membrane sources, like the plasma membrane (PM), is still difficult to integrate in a global picture. Here we show that ER–plasma membrane contact sites are mobilized for autophagosome biogenesis, by direct implication of the tethering extended synaptotagmins (E‐Syts) proteins. Imaging data revealed that early autophagic markers are recruited to E‐Syt‐containing domains during autophagy and that inhibition of E‐Syts expression leads to a reduction in autophagosome biogenesis. Furthermore, we demonstrate that E‐Syts are essential for autophagy‐associated PI3P synthesis at the cortical ER membrane via the recruitment of VMP1, the stabilizing ER partner of the PI3KC3 complex. These results highlight the contribution of ER–plasma membrane tethers to autophagosome biogenesis regulation and support the importance of membrane contact sites in autophagy. Synopsis Early autophagic markers are recruited to endoplasmic reticulum‐plasma membrane (ER‐PM) contact sites established by tethering factors extended synaptotagmins, allowing for local phosphatidylinositol‐3‐phosphate synthesis and autophagosome biogenesis. Autophagy induction is accompanied by ER‐PM contact site mobilization. E‐Syt2, a major tethering protein of ER‐PM contact sites, forms a complex with VMP1 and Beclin1, two regulators of PI3KC3 complex activity. Local autophagosome biogenesis is initiated by local PI3P synthesis via the targeting of PI3KC3 complex at ER‐PM contact sites. Graphical Abstract Early autophagic markers are recruited to endoplasmic reticulum‐plasma membrane (ER‐PM) contact sites established by tethering factors extended synaptotagmins, allowing for local phosphatidylinositol‐3‐phosphate synthesis and autophagosome biogenesis.